Wear and tribological characterization of nickel matrix electrodeposited composites: A review - Sajjadnejad, Mohammad; Haghshenas, Seyyed Mohammad Saleh; Badr, Parnia; Setoudeh, Nader; Hosseinpour, Saman (Wear, 2021)
Electrodeposited metal matrix composite coatings (MMCs) often exhibit superior surface characteristics including corrosion resistance in a wide range of temperatures, improved physical, mechanical, and tribological properties, tunable surface hydrophobicity, and desirable look. Therefore a wide range of studies has been performed so far to assess the diverse physical, mechanical, chemical, electrochemical, and thermal properties of electrodeposited composite coatings that are fabricated on various substrates, under different electrodeposition conditions. In particular, nickel-based composite coatings reinforced with embedded particles (e.g., oxides, carbides, nitrides, and solid-state lubricants) are among the most studied MMCs because of their industrial applications as protective and corrosion-resistant coatings with desirable wear and friction properties. In this review, we provide an extensive overview of the fabricated electrodeposited nickel-based composite coatings which are assessed for their improved wear resistance. The tribological and wear properties of the composite coatings such as weight loss, wear rate, friction coefficient, surface hardness and roughness, as well as their underlying wear mechanisms, will be discussed as a function of the type, content, size, and distribution of the reinforced particles under different electrodeposition parameters such as type and magnitude of applied current, bath composition, pH, temperature, ultrasonication, and presence of surfactants. The quantitative coating characteristics that are tabulated in this review serve as a reference for the researchers in this field and enable the quick selection of coatings and electrodeposition parameters for the desired application.
Keywords: Electrodeposition; Composite coatings; Wear; Tribology